High-grade anal intraepithelial neoplasia is associated with HIV-1 RNA rectal shedding in virologically suppressed MSM. (15th May 2018) - García-Payá, Elena; Fernández, Marta; Padilla, Sergio; García, José A.; Robledano, Catalina; de la Tabla, Victoria Ortiz; Gutiérrez, Félix; Masiá, Mar
Abstract : Objective: The protective effect of ART has not yet been definitively established in MSM. We aimed to characterize the factors associated with persistent HIV-1 RNA rectal shedding. Methods: Prospective study including virologically suppressed MSM from an HIV cohort. High-resolution anoscopy (HRA) was performed for screening of anal dysplasia, and rectal sampling for HIV-1 RNA quantification and sexually transmitted infections (STIs) investigation through multiplex PCR. Both generalized linear mixed (GLM) and zero-altered negative binomial (ZANB) models were performed. Results: One hundred and fifty-five rectal swab samples from 132 virologically suppressed MSM were included. HIV-1 RNA was detectable in 61 (39.3%) samples, with median (IQR) rectal viral load (rVL) of 295.8 (158.8–522) copies/swab. Multivariable GLM showed that the presence of high-grade anal intraepithelial neoplasia (HG-AIN; OR 2.85 [95% CI 1.10–7.38]) and a protease inhibitor-based regimen (OR 2.49 [0.98–6.34]) resulted in increased risk for rectal HIV-1 shedding, whereas higher nadir CD4 + /CD8 + T-cell ratio (OR 0.18 [0.04–0.93]) was negatively associated with rectal shedding. ZANB analyses showed that the best predictors of having detectable rVL were lower nadir CD4 + /CD8 + T-cell ratio (OR 0.98 [0.96–0.99]) and PI-based regimens (OR 4.85 [1.29–18.24]); the presence of HG-AIN (RR 2.50 [1.41–4.45]), and a higher burden of STIs (RR 1.39 [1.03–1.85]) were predictors of rectal HIV-1 shedding intensity. Conclusion: The prevalence of HIV-1 RNA rectal shedding is high in virologically suppressed MSM. In addition to ART and the immune system integrity, local factors, including the co-existence of HG-AIN and the burden of STIs, may account for the persistence of HIV-1 RNA shedding in rectal mucosa.